2014
DOI: 10.1017/s1355617714000782
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Rehabilitation Multi-family Group Intervention for Individuals with Mild Cognitive Impairment and Their Care-Partners

Abstract: There is increasing need for early, pro-active programs that can delay dementia diagnosis and enhance well-being of individuals with mild cognitive impairment (MCI) and their care-partners (i.e., care-dyads). This randomized controlled trial evaluated the efficacy of a combined cognitive rehabilitation and multi-family group treatment (CR-MFG) that was designed to facilitate adoption of newly learned cognitive strategies into the care-dyads everyday lives. Analyzed data included 23 care-dyads who participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…Olchik et al [53] compared measurements with healthy controls and found that verbal fluency and behavioral memory improved significantly. Furthermore, Schmitter-Edgecombe and Dyck [56] found that patients improved some of their memory scores better than controls; the same was found by Suzuki et al [58].…”
Section: Skills Training Trialsmentioning
confidence: 54%
“…Olchik et al [53] compared measurements with healthy controls and found that verbal fluency and behavioral memory improved significantly. Furthermore, Schmitter-Edgecombe and Dyck [56] found that patients improved some of their memory scores better than controls; the same was found by Suzuki et al [58].…”
Section: Skills Training Trialsmentioning
confidence: 54%
“…Three studies used interventions with a combination of cognitive strategy training, psychoeducation, and social skills training components (Joosten-Weyn Banningh et al 2011; Joosten-Weyn Banningh et al 2013; Schmitter-Edgecombe and Dyck 2014). Two studies (Hwang et al 2012; Law et al 2014) utilized interventions with computerized and non-computerized cognitive training components.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies saw improvement on ADL rating scales with cognitive plus physical interventions (Kurz et al 2009; Lam et al 2015) and one saw positive impact with cognitive plus psychological interventions (Tsolaki et al 2011). Schmitter-Edgecombe and Dyck (2014), using cognitive plus psychological interventions, found improvements on performance-based measures of ADLs involving bill-paying and money management activities. Two studies utilizing the Bayer-ADL scale (B-ADL; Hindmarch et al 1998) saw inconsistent improvement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations